(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In the developed world, where obesity and diabetes are epidemics, the role of insulin resistance and its consequences are becomingincreasingly important. Understanding insulin's involvement in a wide range of physiological processes, as well as its actions at themolecular and cellular levels as well as throughout the body, has significant implications for most chronic diseases that are currentlyprevalent in Western populations.Following a discussion of insulin resistance and its associated clinical manifestations, this review provides an overview of insulin'shistory, structure, synthesis, secretion, actions, and interactions. The physiological, environmental, and pharmacological influences oninsulin action and insulin resistance, as well as the clinical syndromes associated with insulin resistance, are some of the specific areasof focus. Other areas of focus include the actions of insulin and manifestations of insulin resistance in particular organs and tissues.We must consider the significant social shifts that have occurred over the past century in terms of physical activity, diet, work,socialization, and sleep patterns, despite our limited comprehension of the intricate biological mechanisms underlying insulin actionand insulin resistance. Obesity, diabetes, and the co-morbidities that go along with them have become epidemics as a result of rapidglobalization, urbanization, and industrialization. This is because inactivity and a lack of balance in one's diet reveal hidden genetictraits that can lead to obesity and diabetes.A clinical condition known as insulin resistance is one in which an impaired biologic response is caused by either a normal or elevatedinsulin level. Specifically, insulin-stimulated glucose disposal is the biologic response that has received the most research, but thespecific cellular mechanism that is responsible for it is unknown. However, insulin resistance is present for a significant amount of timeprior to the onset of clinical hyperglycemia and the diagnosis of Type 2 diabetes. At this stage, insulin resistance appears to be stronglylinked to a group of cardiovascular risk factors that put the person at increased risk for cardiovascular disease. The clinical insulinresistant state and an overview of insulin resistance will be discussed.